Revision of the Megaperidae Manter, 1934 n. comb. (Syn. Apocreadiidae Skrjabin, 1942) including a reorganization of the Schistorchiinae Yamaguti, 1942 - Blend, Charles K.; Karar, Yasser F. M.; Dronen, Norman O. (Zootaxa, 2017)
Modified and/or new keys to the four subfamilies now recognized within the Megaperidae Manter, 1934 n. comb. (Syn. Apocreadiidae Skrjabin, 1942) as well as the genera within each subfamily are presented. Two new genera, Paraschistorchis n. gen. and Plesioschistorchis n. gen., both within the Schistorchiinae Yamaguti, 1942, are erected and keys are provided to the species considered in both new genera—distinguished by possessing caeca that end either in separate ani or blindly. Plesioschistorchis callyodontis (Yamaguti, 1942) n. comb. and Plesioschistorchis haridis (Nagaty, 1957) n. comb. are re-described from new material collected from the common parrotfish, Scarus psittacus Forsskål (Perciformes: Scaridae), inhabiting the Red Sea off Egypt; S. psittacus represents a new host record for both species. The taxonomic status of Schistorchis sensu stricto Lühe, 1906 is examined and revised, a key to the four species we consider in this genus offered, and the monotypic genus Megacreadium Nagaty, 1956 declared a junior synonym of Schistorchis. Members of Schistorchis sensu stricto possess a unique “complex” (i.e. highly cellular/glandular) instead of “simple” (i.e. entirely muscular) type of oral sucker that is quite large in relation to body size; an elongate, somewhat sub-rectangular-shaped body; 5+ testes arranged in at least two rows; caeca that open via separate ani; a long post-testicular region; a median genital pore either at the anterior margin of or just anterior to the ventral sucker; and species of Schistorchis sensu stricto parasitize the intestine of marine fish within the Order Tetraodontiformes Berg. With the revision of this genus, we re-describe Schistorchis carneus Lühe, 1906 from the lower and mid-intestine of the white-spotted puffer, Arothron hispidus (Linnaeus) (Tetraodontiformes: Tetraodontidae), collected in the Red Sea off Egypt. Finally, a plea is made for further study of the Megaperidae n. comb. focusing, in particular, on the following: (1) obtaining new type/voucher materials of Plesioschistorchis manteri (Gupta & Tandon, 1984) n. comb. and Schistorchis paruchini Kurochkin, 1974; (2) elucidating the life histories (i.e. intermediate hosts) of members of the Postporinae Yamaguti, 1958 and Schistorchiinae; and (3) generating DNA sequence data for more species of megaperids to help future workers produce increasingly accurate taxonomic classifications that better reflect phylogenetic relationships within this ecologically diverse group of digeneans.